Study of Vibrio anguillarum strains from different sources with emphasis on ecological and pathobiological properties. - Larsen, J L (1988)
A total of 317 Vibrio anguillarum strains were isolated from water, sediment, and diseased as well as healthy rainbow trout at a Danish mariculture farm and from feral fish caught close to the farm. All strains were examined serologically. Ten sera permitted determination of the O group in 66.7% of the strains from diseased rainbow trout. Furthermore, the O group could be determined in 45.1 to 65.4% of the strains from mucus, gills, and intestinal contents of healthy rainbow trout, while only 22.2 to 28.8% of the isolates from water, sediment, and gills or mucus of feral fish were groupable. Serogroup O1 and to some extent O2 appeared to be associated with trout. Strains from these serogroups were selected for analyses of hemagglutinating activity and surface hydrophobicity. Serogroup O1 comprised hemagglutinating as well as nonhemagglutinating strains; from cases of vibriosis, all O1 strains were nonhemagglutinating. The strains belonging to serogroup O2 were generally hemagglutinating. Examinations of surface hydrophobicity by salt aggregation and hydrophobic interaction chromatography suggested that the O1 strains were more hydrophobic than the O2 strains. In pathogenicity tests, O1 strains isolated from gills and mucus of healthy rainbow trout killed all trout in the test groups. A strain from the intestinal contents of healthy rainbow trout did not produce significant mortality. This strain could, however, be frequently reisolated from the pronephros of fish in the test group concerned. After challenge with strains from eel mucus and seawater, mortality was not produced, and furthermore, these strains could not be reisolated from the pronephros.